Christian Democracy in the European Union (1945-1995) : proceedings of the Leuven Colloquium, 15-18 November 1995 - Lamberts, Emiel (Leuven : University Press, 1997)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: christendemocratie; Europese Unie (EU).